Deformation of samples of silumin AK5M2 doped with titanium by irradiation of the film/substrate system with a pulsed electron beam; Materials in External Fields ((ISMEF 2022) ) - Ivanov Yu. F. Yuriy Fedorovich; Klopotov A. A. Anatoly Anatoljevich; Zagulyaev D. V. Dmitry Valerjevich; Ustinov A. M. Artem Mikhaylovich; Prokopenko N. A. Nikita Andreevich; Teresov A. D. Anton Dmitrievich; Abzaev Yu. A. Yury Afanasjevich; Klopotov V. D. Vladimir Dmitrievich (2022, 2022)
Title screen